Oceanic Encounters Exchange, Desire, Violence - Jolly, Margaret; Tcherkézoff, Serge; Tryon, Darrell (ANU Press, 2009)
This volume, the result of ongoing collaborations between Australian and French anthropologists, historians and linguists, explores encounters between Pacific peoples and foreigners during the longue durée of European exploration, colonisation and settlement from the sixteenth century to the twentieth century. It deploys the concept of 'encounter' rather than the more common idea of 'first contact' for several reasons. Encounters with Europeans occurred in the context of extensive prior encounters and exchanges between Pacific peoples, manifest in the distribution of languages and objects and in patterns of human settlement and movement. The concept of encounter highlights the mutuality in such meetings of bodies and minds, whereby preconceptions from both sides were brought into confrontation, dialogue, mutual influence and ultimately mutual transformation. It stresses not so much prior visions of 'strangers' or 'others' but the contingencies in events of encounter and how senses other than vision were crucial in shaping reciprocal appraisals. But a stress on mutual meanings and interdependent agencies in such cross-cultural encounters should not occlude the tumultuous misunderstandings, political contests and extreme violence which also characterised Indigenous-European interactions over this period.